Self-powered and broadband opto-sensor with bionic visual adaptation function based on multilayer γ-InSe flakes - Liu, Weizhen; Yang, Xuhui; Wang, Zhongqiang; Li, Yuanzheng; Li, Jixiu; Feng, Qiushi; Xie, Xiuhua; Xin, Wei; Xu, Haiyang; Liu, Yichun (Light, science & applications, 2023)
Visual adaptation that can autonomously adjust the response to light stimuli is a basic function of artificial visual systems for intelligent bionic robots. To improve efficiency and reduce complexity, artificial visual systems with integrated visual adaptation functions based on a single device should be developed to replace traditional approaches that require complex circuitry and algorithms. Here, we have developed a single two-terminal opto-sensor based on multilayer γ-InSe flakes, which successfully emulated the visual adaptation behaviors with a new working mechanism combining the photo-pyroelectric and photo-thermoelectric effect. The device can operate in self-powered mode and exhibit good human-eye-like adaptation behaviors, which include broadband light-sensing image adaptation (from ultraviolet to near-infrared), near-complete photosensitivity recovery (99.6%), and synergetic visual adaptation, encouraging the advancement of intelligent opto-sensors and machine vision systems. A single two-terminal opto-sensor based on multilayer γ-InSe flakes was developed and successfully emulated human-eye-like adaptation behaviors, which could motivate the further development of advanced opto-sensors and artificial visual systems.